Rancang Bangun Aplikasi Augmented Reality pada Komponen Komputer sebagai Media Pembelajaran Berbasis Mobile - Rimo Handriyatma; Muhammad Anwar (Ranah Research : Journal of Multidisciplinary Research and Development, 2021)
Based on observations at SMK Negeri 2 Lubuk Basung, especially in the Computer Assembly subject, teachers have not used instructional media as learning process activities. The learning media that are used are still in the form of text and images using Microsoft Office PowerPoint software which makes students less understanding of understanding learning material and makes students bored and bored so the learning process activities are not optimal. The application of Augmented Reality as a learning medium aims to attract students' attention and make it easier for students to understand the material in the learning process of computer assembly, for example in practical lessons. Making applications using Mobile-based Java programming with the Unity application software version (2018.2.5f1) and Vuforia support version (2018.2.5f1). The features contained in the Augmented Reality application are AR Camera, Material, Exercise, Quiz, About, and Exit.